Results of concrete absorption test related to some particular factors - Wawrzeńczyk, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
In spite of the fact that common concrete absorption tests are technically simple, the correctness of received results is still very disputable. The lack of unequivocal procedures makes it impossible to compare the results obtained in various laboratories. The paper presents the research results received in 5 series of concrete with three different cements and various w/c ratios. The investigations were conducted on cube specimens with dimensions of 10cm and 15cm, all cubes were soaked and dryed in long terms. The object of the research was to identify the effect of specimens dimensions and soaking time on the concrete absorption. Soaking time applied to investigations vastly exeeds the common soaking time described in standards concerning precast concrete elements.